Severe hypercalcemia from sarcoidosis with a non-suppressed parathyroid hormone and “positive” parathyroid scan - Marc Cillo (Journal of Clinical and Translational Endocrinology Case Reports, 2023)
Background/Objective: Sarcoidosis can cause severe hypercalcemia and is often a challenge to diagnose due to its variable clinical and radiographic presentations. Severe hypercalcemia is considered an emergency, where prompt treatment is necessary to minimize risk of end organ complications. Case report: I present a case of a 65-year-old woman who presented with manifestations of severe hypercalcemia, including acute kidney injury and confusion, with a non-suppressed intact parathyroid hormone (PTH) level and a technetium 99 m sestamibi parathyroid scan with single photon emission computed tomography (SPECT) showing bilateral intrathyroidal tracer uptake concerning for multiple possible parathyroid adenomas. 1,25-dihydroxyvitamin D was elevated but conventional chest radiography was unremarkable. Subsequent evaluation involving chest computed tomography (CT) and endobronchial biopsy resulted in findings consistent with sarcoidosis. Prednisone 40 mg by mouth once daily was initiated, and 3 months after initial evaluation, the serum calcium and creatinine normalized, as did neurological function. Discussion: Severe hypercalcemia should always be evaluated urgently with an exhaustive evaluation to avoid a delay in the diagnosis and/or treatment of potentially serious underlying medical conditions and to avoid performing potentially unnecessary interventions In these cases, a non-suppressed PTH level does not necessarily rule out PTH-independent causes, a “positive” parathyroid scan does not automatically rule in primary hyperparathyroidism, and negative conventional chest radiography does not rule out sarcoidosis. Conclusion: Diagnostic algorithms for severe hypercalcemia can be utilized as a guide for the evaluation, but caution should be advised when they are taken as a rule. Understanding the limitations and pitfalls of diagnostic imaging and laboratory assays are essential, especially when they do not correlate with the clinical presentation.